The Effect of Employee Performance on Consumer Satisfaction at Setia Hotel, Puruk Cahu, Murung Raya - Alexandro, Rinto (International Journal of Social Science and Business, 2021)
Employee performance is what employees do or don't do so that they affect the company's contribution, including the quality services provided. Employee performance is one of the main assets that must be owned by the company, especially the hotel business where the aim is to measure customer satisfaction. Quality performance will create comfort to consumers from that comfort that creates a sense of satisfaction for consumers. This study aims to: Knowing how big the influence of employee performance on customer satisfaction at Hotel Setia Puruk Cahu Murung Raya. The research approach used is quantitative with data collection techniques through: Observation, Interview, and Questionnaire/Questionnaire. Data analysis techniques: Simple Linear Regression Test, Hypothesis Test (t test) and Determination Test (R Square test). From the results of the analysis that the researchers did, it can be seen that the results of the Simple Linear Regression test show that Based on table 4.20 above, it can be understood that: Constant a = 3.936 and coefficient b = 0.441 so that the simple regression equation becomes Y = 0.441 + 3.936X constant a is 3.936 The regression coefficient for X is 3.936 which states that each addition of one unit of X variable will increase consumer satisfaction by 0.441 or 44.1%, the coefficient is positive. While the results of the hypothesis test show that tcount on employee performance is 4,328 at degrees of freedom (df) = N-2 = 43-2 = 41, then the ttable is determined at 1.217. So it can be concluded that tcount > ttable (4,328 > 1,217). Then it can be concluded that tcount > ttable (4,328 >1.217).